2015
DOI: 10.1007/s10534-015-9905-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved cytotoxicity of pyridyl-substituted thiosemicarbazones against MCF-7 when used as metal ionophores

Abstract: Zinc is the second most abundant transition metal in the human body, between 3 and 10% of human genes encoding for zinc binding proteins. We have investigated the interplay of reactive oxygen species and zinc homeostasis on the cytotoxicity of the thiosemicarbazone chelators against the MCF-7 cell line. The cytotoxicity of thiosemicarbazone chelators against MCF-7 can be improved through supplementation of ionic zinc provided the zinc ion is at a level exceeding the thiosemicarbazone concentration. Elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…On the other hand, it has been reported that Dp44mT and their complexes with iron and copper cause apoptosis by generating cytotoxic ROS [ 23 , 40 ]. Moreover, Akladios et al reported that in some TSC, the addition of metal cations may increase activity [ 41 , 42 ]. This observation led to the alternative use of TSC as ionophores.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that Dp44mT and their complexes with iron and copper cause apoptosis by generating cytotoxic ROS [ 23 , 40 ]. Moreover, Akladios et al reported that in some TSC, the addition of metal cations may increase activity [ 41 , 42 ]. This observation led to the alternative use of TSC as ionophores.…”
Section: Introductionmentioning
confidence: 99%